Vertex Search Algorithm of Convex Polyhedron Representing Upper Limb Manipulation Ability - Sasaki, Makoto; Iwami, Takehiro; Miyawaki, Kazuto; Sato, Ikuro; Obinata, Goro; Dutta, Ashish (IntechOpen, 2011)
None